Cinsel Gelişim Bozukluğu Olan Çocuk ve Adolesanların Sınıflandırılması ve Klinik Özelliklerinin Değerlendirilmesi - Erdoğan, Sema (My University, 2009)
Amaç: LWPES/ESPE'nin önerdiği yeni tanımlayıcı sınıflandırmaya göre, birimimizde takip edilen CGB'li olguların etiyolojik dağılımını belirlenmek ve klinik özelliklerini değerlendirilmekHastalar ve Yöntem: Haziran 2006- Haziran 2009 tarihleri arasında takip edilen CGB'li hastaların dosya kayıtları geriye dönük olarak incelendi. Hastalar karyotip sonucuna göre 3 ana tanı grubundan (46,XX CGB, 46,XY CGB ve seks kromozomu CGB) birine ayrıldı. Klinik, laboratuvar, görüntüleme ve patoloji sonuçlarına göre konulan özgül tanılarla etiyolojik dağılım belirlendi.Bulgular: Çalışmaya alınan toplam 95 olgunun 24'ü 46,XX CGB, 45'i 46,XY CGB ve 26'sı seks kromozomu CGB olarak saptandı. Her grubun etiyolojik dağılımı tabloda verildi. Başvuruda hastaların 36'sı kız, 22'si erkek, 37'si belirsiz cinsiyetteydi. Cinsiyet seçiminden sonra 56 kız ve 39 erkek hasta belirlendi. Başvuru yaşları 1 gün ile 17.5 yıl arasında değişiyordu; olguların 38'i, bebeklik (< 1 yaş), 22'si çocukluk (1-10 yaş), 35'i adölesan (>10 yaş) dönemde başvurdu. Yenidoğan döneminde başvuran olgu sayısı 28 idi. Hastaların %18'inde akrabalık öyküsü vardı. En sık başvuru nedenleri aşikar kuşkulu genital yapı (n: 22), boy kısalığı (n: 16) ve izole perineal hipospadias (n: 11) idi. KAH'lı hastalar en sık aşikâr kuşkulu genital yapı ile başvuruken, Turner Sendrom'lu hastalarda en sık nedenler boy kısalığı ve amenore, PAİS'lilerde ise perineal hipospadiyas, mikropenis ve kuşkulu genital yapıydı.Sonuçlar: Bu çalışmada yalancı hermafrodit (YH) ve interseks terimlerleri yerine cinsel gelişim bozukluğu terimi kullanılmıştır. Karyotipin esas alınmasıyla, eski sınıflandırmada (dişi YH, erkek YH, gerçek hermafrodit) yer almayan seks kromozomu CGB'nin dahil edilmesi etiyolojik dağılımda önemli değişikliğe neden olmuştur. Turner sendromun yeni sınıflandırmada ağırlıklı yer tutmaktadır. Böylece belirgin genital anormalliği olmayan hastalar ile CGB'nin içeriği genişlemiştir. CGB'li hastalar geniş bir yaş aralığında başvurabilir.

The nomenclature `intersex?, `hermaphrodite? and `pseudohermaphrodite? is anachronistic, unhelpful, and perceived to be pejorative by some affected families. In its place, a consensus statement recommends the term `disorder of sex development? (DSD), a generic definition encompassing any problem noted at birth where the genitalia are atypical in relation to the chromosomes or gonads. The karyotype is used as a prefix to define the category of DSD, replacing the arcane terminology of male or female pseudohermaphroditism (now known as XY DSD or XX DSD, respectively). The professional societies representing paediatric endocrinology ? primarily the European Society for Paediatric Endocrinology (ESPE) and the Lawson Wilkins Pediatric Endocrine Society (LWPES) ? responded by organizing a consensus meeting on the management of intersex.Aim: The aim of this study is patients with disorders of sex development follow up in Pediatric Endocrinology Department, classifying them as the European Society for Paediatric Endocrinology (ESPE) and the Lawson Wilkins Pediatric Endocrine Society (LWPES) new classification which to be formed in 2006.Materials and Metods: A retrospective study of 95 patients evaluated by the team at Ondokuz Mayıs Uniercity Pediatric Endocrinology Department, from June 2006 through June 2009. The karyotype is used as a prefix to define the category of DSD (46,XX DSD, 46,XY DSD and sex chromozomal DSD). The etiologic classification performed with clinical, laboratory, radiographic and pathology metods.Findings: 95 cases could be categorised as 46,XX DSD (n:24), 46,XY DSD ( n:45) and sex chromosomal DSD (n: 26). The age of patients were between 1 day to 17,5 years, at the beginning 36 were female, 22 male, 37 undetermined. After the gender assignment 56 were female and 39 were male. Patients presented to us below one year 38(28 were newborn), 1-10 years 22, after 10 years 35. Parental consanguinity rate was %18.Most frequent complaint was ambiguous genitalia (n:22), short stature (n:16), perineal hypospadias. Childs with congetal adrenal hyperpasia had ambiguous genitalia, girls with Turner syndrome had short stature and amenorrhea, childs with PAİS had perineal hypospadias and ambiguous genitaliaResults: In this study we used that terminology: Disorder of Sex Development (DSD) instead of pseudohermapfroditizm and intersex. The karyotype is used as a prefix to define the category of DSD. So that Turner Syndrome join the DSD classification and take a big part of sex chromosomal DSD. After this practise patients who where have not have ambiguous genitale must be think inside to DSD table.
Classification and Clinical Evaluation of the Children and Adolescent With Disorders of Sex Development
Keywords: Endokrinoloji ve Metabolizma Hastalıkları; Çocuk Sağlığı ve Hastalıkları; Endocrinology and Metabolic Diseases; Child Health and Diseases